Motion Control System for a Remotely Operated Vehicle with Interval Parameters; International Journal of Mechanical Engineering and Robotics Research; Vol. 6, No. 5 - Gaivoronsky (Gayvoronsky) S. A. Sergey Anatolievich (2017, 2017)
Title screen